The relationship between the interest rate and infaltion rate in selected countries - Phua, Kheng Leng (Universiti Malaysia Sarawak (UNIMAS), 2012)
This paper revisits the relationship between the interest rate and inflation in selected countries such as Indonesia, Malaysia, Philippines, Singapore and Thailand. I included the data from 1986Q3 to 20 IIQ3 to examine the disparities in empirical regularities governing the interest rate and inflation in these countries. Empirical results show that causality run from interest rate to inflation with positive relationship for Malaysia, Philippines and Thailand, which is partially fit with Fisher effect theory. For short run causality results, Singapore and Malaysia are not having relationship for these two variables. But, the causality of Philippines runs from interest rate to inflation and Thailand runs in opposite direction whiles a bi-directional causality exists for Indonesia. The countries are partially fit the Fisher theory except the Singapore, managing these rates are indeed important policy options in 'promoting macroeconomic stability and sustainability in the region.